AR model for infant pain anxiety recognition using fuzzy k-NN - Muhammad Naufal, Mansor; Syahryull Hi-Fi Syam, Ahmad Jamil; Muhammad Nazri, Rejab; Addzrull Hi-Fi Syam, Ahmad Jamil (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org